2015
DOI: 10.1016/j.joep.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Investor happiness

Abstract: We study investor happiness in a panel survey of brokerage clients at a UK bank. When investors anticipate future happiness, they set their return aspirations according to personal portfolio risk, objectives, investment horizon, confidence, and other individual characteristics. They are accurate in their forecasts, only rarely are investors unhappy with outcomes they predicted they would be happy with, and vice versa. However, determinants of experienced happiness only partially correspond to the ones found fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Happiness may positively influence investment decisions, although it is not statistically significant. Happy people are more optimistic about the future and more confident in making investment decisions [20,21]. However, this effect is not statistically significant, and people tend to ignore the future when making investment decisions [22].…”
Section: Resultsmentioning
confidence: 99%
“…Happiness may positively influence investment decisions, although it is not statistically significant. Happy people are more optimistic about the future and more confident in making investment decisions [20,21]. However, this effect is not statistically significant, and people tend to ignore the future when making investment decisions [22].…”
Section: Resultsmentioning
confidence: 99%
“…An early work about investor happiness has been the study of Merkle et al (2015). To be more precise, they use a panel survey of brokerage clients at a UK bank for the purposes of examining investor happiness.…”
Section: Studies About Investment Decisions Linked With Happiness And...mentioning
confidence: 99%
“…Investors tend to experience life satisfaction when they feel good about their investment endeavours (Diener, 2000). Merkle et al (2015) found that investors tend to be happy when they achieve investment success through active decision making rather than passive decision making. Diener and Ryan (2009) state that individuals compare themselves with others to establish whether or not their lives are satisfactory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ultimately, investor risk-taking behaviour and perception, life satisfaction, and demographics all contribute towards establishing an investor's risk tolerance and overall financial behaviour (Dickason, 2017;Diener & Ryan, 2009; J. Grable & Joo, 2000;Merkle et al, 2015;Vanguard, 2019). Therefore, it is important for investors and investment companies to be aware of these factors and how risk tolerance can influence investors' financial endeavours.…”
Section: Literature Reviewmentioning
confidence: 99%